Magnitudes and capital key divergence of the Eurosystem's PSPP/PEPP purchases - Update December 2021 - Carlo Birkholz; Friedrich Heinemann (ZEW - Leibniz Centre for European Economic Research, 2021)
The ECB Council has to take a decision on the future of its asset purchase programmes as the monetary crisis support that was appropriate in the early phase of the pandemic needs to be adjusted to new circumstances. The changing environment is characterized by an advanced recovery from the pandemic contraction and by new growth obstacles such as shortages of important inputs. With these changes, initially convincing arguments for extraordinary monetary policy supports are losing their strength. Against this background, this study updates an earlier quantitative analysis on the conduct of both the PEPP and the PSPP since the outbreak of the pandemic. For PSPP/PEPP purchases between March 2020 and September 2021, this expertise assesses the size of purchase flows and stocks, country allocations and their proportionality to the ECB capital key, and their magnitude relative to GDP and public debt.
Keywords: 330